Recovery of FTO coated glass substrate: Via environment-friendly facile recycling perovskite solar cells - Chowdhury M.S.; Rahman K.S.; Selvanathan V.; Hasan A.K.M.; Jamal M.S.; Samsudin N.A.; Akhtaruzzaman M.; Amin N.; Techato K. (Royal Society of Chemistry, 2023)
Cost effectiveness; Glass; Molecular biology; Nanocomposites; Perovskite; Physicochemical properties; Recycling; Solar power plants; Substrates; Tin oxides; Toxic materials; Coated glass substrates; Conductive glass; Device architectures; Environment friendly; Fluorine doped tin oxide; Individual components; Organic-inorganic; Photovoltaic devices; Perovskite solar cells